ANALISIS FAKTOR MANUSIA TERHADAP KEJADIAN KECELAKAAN KERJA PADA PEKERJA DI UNIT SPINNING V INDUSTRI TEKSTIL - Saarah Tiwi Anjani; MG. Catur Yuantari (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Work accident can occur in all areas of work, including work in the areas of textileand spinning (spinning of yarn). X Factory is a national company that has 5 unitsof spinning production process that has changed the raw cotton into yarn with thehelp of various machine work and machine operators. The purpose of this studywas to analyze the factors the causes of human factors side of events work accidenton worker in Spinning Unit V X Factory.This type study was quantitative approach by using cross sectional study design.The population in this study was the workers in the unit spinning V Factory Beamas many as 446 people with samples as much as 79 respondents. Study instrumentused questionnaires and processed using the spearman rank test.Statistical results can be concluded that there was no relationship between thelevel of knowledge (p 0.669), work experience (p 0.571), the level of physicalcondition (0.397) and work motivation (p 0.629) with a work accident on worker inSpinning unit V. However, there was a relationship between the level of psychologicalconditions (p 0.047) against a work accident on worker in Spinning unit VX Factory.Every worker at X Factory mandatory regulations regarding safety and occupationalhealth that exist within the company. Especially workers in the productionthat always work using equipment or machine work, to always implement theHSE culture while working to avoid an unwanted stuff while working.Keywords: accidents, workers-unit Spinning V, human factors